Conditioning factors for nurses to defend the autonomy of the elderly on the terminality of life - Rafael Barroso Gaspar; Marcelle Miranda da Silva; Karen Gisela Moraes Zepeda; Ítalo Rodolfo Silva
ABSTRACT Objective: to understand the meanings attributed by nurses about conditions that interfere in defending of the elderly's autonomy on the terminality of life in the context of hospitalization. Method: qualitative and exploratory study, which applied the Grounded Theory. Data were collected between November 2016 and May 2017, in the internal medicine wards of a hospital in Rio de Janeiro, Brazil, through non-participant observation and semi-structured interviews. Three sample groups composed of ten nurses, eight doctors, and 15 nursing technicians were investigated. Results: the conditions are related to the medical power, subordination of nurses, family influences; the functional decline of the elderly; and biomedical model. Final considerations: the elderly's autonomy is veiled and violated since their abilities are subjugated, and the family's will and professional paternalism may prevail. However, this right must guide contemporary care models and integrate palliative care.